Optimal antithrombotic therapy after transcatheter aortic valve replacement in patients with atrial fibrillation. (October 2020) - Zeng, Qingchun; Cheng, Zhendong; Xia, Yi; Cheng, Rui; Ou, Ailian; Li, Xinrui; Xu, Xingbo; Huang, Yuli; Xu, Dingli
Atrial fibrillation (AF) is prevalent in patients with aortic stenosis (AS) undergoing transcatheter aortic valve replacement (TAVR). Depending on the timing of AF detection, it is usually categorized as pre-existing AF or new-onset AF. Antiplatelet therapy, rather than a vitamin K antagonist, may be considered as the primary treatment for patients without an indication for oral anticoagulants who undergo TAVR. However, the optimal postprocedural antithrombotic regimen for patients with AF undergoing TAVR remains unknown. In this review, we briefly introduce the management strategies of antithrombotic therapy and list the evidence from related studies to elucidate the optimal antithrombotic management for patients with AF undergoing TAVR.